2017
DOI: 10.3390/su9091558
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Analysis of Charcoal Production in Masonry Kilns with and without Carbonization Process Generated Gas Combustion

Abstract: New technologies and emissions controls have been developed for the production of charcoal, but are not widely used in the industry. The present study seeks to evaluate the potential environmental impact of these new technologies as compared to traditional ones. A Life Cycle Assessment (LCA) of Brazilian charcoal produced with different technologies without and with the combustion of the gases in burners or furnaces was carried out. The inclusion of furnaces for the combustion of gases reduces all categories o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 32 publications
2
17
0
1
Order By: Relevance
“…The study by Berrill et al [15] identified that the increase in renewable sources such as wind and solar in Europe will create positive aspects besides reducing GHG emissions in the coming years. Following this, Miranda-Santos et al [35] worked on stimulating public policies on production sources with lower environmental impacts.…”
Section: Resultsmentioning
confidence: 99%
“…The study by Berrill et al [15] identified that the increase in renewable sources such as wind and solar in Europe will create positive aspects besides reducing GHG emissions in the coming years. Following this, Miranda-Santos et al [35] worked on stimulating public policies on production sources with lower environmental impacts.…”
Section: Resultsmentioning
confidence: 99%
“…The remaining emissions are generated by the combustion of diesel fuel (transport) and electricity production. A similar ratio is given for charcoal production, where ≈61% of GHG emissions are emitted during charcoal production, and the remaining 39% occurred during its usage [40]. Unsustainable biomass growth can decrease savings related to CO 2 emissions.…”
Section: Reductantsmentioning
confidence: 85%
“…Although the carbonization temperature can be recorded and the physicochemical properties of the charcoal may be homogeneous when using masonry and mud kilns, avoidance of the release of pyrolysis gases into the atmosphere is one of the selection criteria (Table 1). Unlike mud kilns, the retorts and converters can be adapted to recover energy and other products from the pyrolysis gases (e.g., liquid condensates, tars, and syngas) while avoiding the direct release of pyrolysis gases into the atmosphere [54]. Nonetheless, retorts and converters are tailored for the use of forest biomass as feedstock (e.g., logs, large pieces of wood).…”
Section: Technological Alternatives For the Conversion Of Agricultural Waste Into Biochar In The Studied Farmers' Cooperativesmentioning
confidence: 99%
“…-Increases methane yield when used as an additive in anaerobic digestion systems. [53,54,[90][91][92] Green infrastructure -When used as a substrate in rooftop and vertical gardens, decreases the weight and corresponding load of these infrastructures. -Preserves the ecosystems services linked to urban greenery (when used as a soil conditioner).…”
Section: Potential Applications Of Biochar In the Neamentioning
confidence: 99%